Exopeptidase combination enhances the degradation of isotopically labelled gluten immunogenic peptides in humans - Mourabit, Sulayman; Römer, Sarah; Bonner, Erin R.; Winter, Fabian; Tschollar, Julian; Tzvetkov, Mladen V.; Weitschies, Werner; Engeli, Stefan; Tschollar, Werner (Frontiers in Immunology, 2024)
Introduction. Celiac disease is a common autoimmune-like enteropathy caused by an aberrant response to incompletely digested dietary gluten. Gluten immunogenic peptides including the immunodominant 33-mer are thought to be resistant to proteolytic digestion by human gastrointestinal peptidases. We developed a novel enzyme therapy approach to support gluten peptide digestion using a combination of two tandem-acting exopeptidases, AMYNOPEP, that complement the intrinsic enzymatic activity of intestinal brush border enterocytes. Methods. We evaluated the effects of AMYNOPEP supplementation on 33-mer degradation in vitro and in vivo. In a cross-over clinical study, healthy volunteers with no gastrointestinal disorders were given stable isotope (SI) labelled 33-mer peptides in the presence of varying peptide substrates and caloric loads, with and without AMYNOPEP. 33-mer degradation products (SI-labelled single amino acids) were measured in the blood plasma using LC-MS/MS. Results. AMYNOPEP achieved rapid, complete amino-to-carboxyl terminal degradation of the 33-mer in vitro, generating single amino acids and dipeptides. In healthy volunteers, AMYNOPEP supplementation significantly increased 33-mer degradation and absorption of SI-labelled amino acids even in the presence of competing substrates. Specifically, we observed a 2.8-fold increase in the Cmax of stable isotope-labelled amino acids in the presence of wheat gluten. The absorption kinetics of labelled amino acids derived from 33-mer digestion with AMYNOPEP closely resembled that of SI-labelled X-Proline dipeptides administered without enzyme supplementation, highlighting the rapid hydrolytic activity of AMYNOPEP on polypeptides. Conclusions. AMYNOPEP achieved complete degradation of the 33-mer into single amino acids and dipeptides in vitro and significantly improved 33-mer degradation kinetics in healthy volunteers, as measured by labelled amino acid detection, warranting further investigation into the potential therapeutic benefits of exopeptidase combinations for patients with gluten-related health disorders including celiac disease.